The role and diagnostic value of deregulated miRNAs in cervical cancer - Masoumeh Parvizi; Maryam Vaezi; Farhad Jeddi; Masoumeh Bakhshandeh; Reza Eghdam-Zamiri; Noushin Mobaraki-Asl; Ebrahim Esmati; Abbas Karimi (Discover Oncology)
Abstract Cervical cancer (CC) remains a significant global health concern, particularly affecting women in low-income countries. Despite advancements in screening programs, CC continues to pose a substantial mortality risk, highlighting the need to explore diagnostic and treatment modalities. This review focuses on the role of deregulated microRNAs (miRNAs) in CC development, emphasizing their potential as biomarkers for early detection and prognosis in body fluids. miRNAs have emerged as critical regulators of key cellular processes, including proliferation, migration, invasion, and apoptosis, and their dysregulation is closely linked to CC progression. Upregulated miRNAs such as miR-146b-3p, miR-1908, and miR-21 promote CC progression by targeting tumor suppressor genes, while downregulated miRNAs like miR-23-3p and miR-4262 are associated with reduced tumor aggressiveness. miRNAs also hold significant promise as non-invasive prognostic biomarkers. Their expression levels correlate with clinical outcomes, including tumor stage, metastasis, and overall survival, making them valuable tools for risk stratification and personalized treatment strategies. Liquid biopsies, which detect circulating miRNAs in bodily fluids, offer a minimally invasive approach to monitor tumor dynamics and predict patient outcomes. Furthermore, exosomal miRNAs are emerging as promising diagnostic and prognostic tools for CC. Advanced diagnostic technologies and bioinformatics tools are anticipated to enhance the identification of evident miRNA biomarkers in the clinical settings. Standardized protocols for sample collection and analysis will improve the reproducibility of miRNA studies, while a deeper understanding of miRNA biology may unlock their potential as therapeutic targets. In conclusion, this review consolidates current research on deregulated miRNAs in CC, highlighting their diagnostic and prognostic significance. The findings underscore the potential of miRNAs to revolutionize CC management through innovative diagnostic and therapeutic strategies.